MODEL OF LOCAL GOVERNMENT IN INDONESIA: WHAT DOES THE 1945 CONSTITUTION INTEND? - Inna Junaenah (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2021)
The character of the current local government in Indonesia is moving forward to re-centralisation instead of decentralisation. Meanwhile, some comparative studies on models of local governments are catching eyes as they attempt to systemise a classification. This paper aims to describe a legal doctrinal assessment of the model of local government in Indonesia. It also gives some options for a separate comparative study, if it needs an ‘apple to apple’ or an inspiring object of study, to achieve the purposes of comparison for better legislation constituting local government in Indonesia. In doing so, the previous studies on global models of local government are examined to assess the current Indonesian legislations, covering the nature of the legal entity, source of authority and financial, organisation, and the extent in making the decision. This study points that the recent model of local government in Indonesia is a hybrid system, which implies close to Franco rather than the Anglo model, with certain specifications. However, the 1945 Constitution contains some future and global values without disregarding the root of local government function in the community. Therefore, the study considers the normative model of local government in Indonesia inconsistent with the legal policy in the 1945 Constitution. It is then considerable if an amendment of the local government Act is an option to re-modify the model of local government, which can reflect the ideas in the Constitution and is not left behind the global trends. Abstrak: Karakter Pemerintahan Daerah yang Nampak hari ini di Indonesia lebih mengarah pada re-sentralisasi daripada desentralisasi. Sementara itu, beberapa kajian perbandingan mengenai model-model pemerintahan daerah cukup menarik untuk dapat dilihat bagaimana untuk mengklasifikasi suatu sistematisasi. Dalam tulisan ini hendak dipaparkan sudut pandang yuridis-normatif terhadap model Pemerintahan Daerah di Indonesia. Termasuk di dalamnya terdapat suatu pilihan untuk studi perbandingan, apakah dibutuhkan syarat suatu kesetaraan atau syarat suatu objek kajian yang dapat mengispirasi, untuk mencapai tujuan perbandingan yaitu penyempurnaan suatu hukum yang mengatur Pemerintahan Daerah di Indonesia. Untuk itu, kajian-kajian terdahulu mengenai model-model Pemerintahan Daerah secara global telah ditelaah berikutnya sebagai bahan untuk dapat mencermati peraturan perundang-undangan di Indonesia, yang meliputi makna entitas hukumnya, sumber kewenangan dan keuangan, kelembagaan dan sejauh mana untuk menentukan keputusan. Ditemukan bahwa model Pemerintahan Daerah di Indonesa merupakan system hybrid, yang lebih mendekati model Franco dibandingkan dengan model Anglo beserta spesifikasi di dalamnya. Bagaimanapun, Undang-Undang Dasar 1945 berisi nilai-nilai masa depan dan global tanpa mengesampingkan akar dari fungsi Pemerintahan Daerah di masyarakat. Dengan patokan seperti itu, model normatif Pemerintahan Daerah di Indonesia tidak sejalan dengan dengan gagasan dalam UUD 1945. Maka dari itu, suatu perubahan terhadap Undang-Undang Pemerintahan Daerah dipandang sebagai suatu upaya yang dapat dipertimbangkan untuk re-modifikasi model Pemerintahan Daeeah dapat mencerminkan gagasan dalam Konstitusi tanpa tertinggal oleh kecenderungan global. Kata Kunci: Perbandingan Pemerintahan Daerah, Desentralisasi, Model Pemerintahan Daerag, UUD 1945 Negara Republik Indonesia